Epigallocatechin-3-gallate conjugated with selenium nanoparticles prevents neurological complications in rats exhibiting schizophrenia-like behaviors - Gamal El-Deen, Hadeer M.; Essawy, Amina E.; Mohammed, Nema A.; Abdelfattah, Mohamed S.; Fathalla, Ayah S.; El-khadragy, Manal F.; Abdel Moniem, Ahmed E. (Frontiers in Pharmacology, 2025)
IntroductionThe main catechin in green tea is a flavonoid called (-)-epigallocatechin 3-gallate (EGCG) that possesses significant biological and pharmacological properties. In a rat model of schizophrenia, we examined the neuroprotective and antipsychotic properties of EGCG conjugated with selenium nanoparticles (EGCG-SeNPs) against neurological complications induced by social isolation, including significant behavioral and neurochemical dysfunctions that mimic the symptoms of schizophrenia in it.MethodsMale rats (21–23 days old) were divided into two groups: the social rearing (SR) group and the social isolation-reared (SIR) group (one rat per cage). The experiment lasted for eight weeks. For the last 2 weeks, rats in both SR and SIR were assigned to saline, EGCG (50 mg/kg), sodium selenite (0.5 mg/kg), EGCG-SeNPs (0.5 mg/kg), and risperidone (2.5 mg/kg) treated groups. At the end of the experiment, all rats were subjected to behavioral tests, and the prefrontal cortex tissues from each group were analyzed for oxidative stress parameters, proinflammatory cytokines, neurochemicals, apoptotic markers, and histopa‐thological changes.ResultsEGCG‐SeNPs treatment improved the behavior of rats, significantly decreased the levels of malondialdehyde, nitric oxide, and the pro-inflammatory mediators TNF-alpha, IL-1beta, and NF-κB, raised the expression of antioxidant glutathione, superoxide dismutase, glutathione reductase, and catalase, enhanced monoaminergic and cholinergic transmission, and restored the excitatory-inhibitory amino acid imbalance. Additionally, EGCG-SeNPs improved the histopathological changes in the prefrontal cortex, upregulated the expression oe Bcl-2, and downregulated the expression of the anti-apoptotic Bax and caspase-3.DiscussionThese encouraging anti-inflammatory, anti-oxidative, anti-apoptotic, and neuromodulatory activities suggest that EGCG-SeNPs might serve as a naturally derived antipsychotic agent.